Behavior of cholinesterase and liver mitochondrial function in dogs submitted to normothermic ischemia and reperfusion - Fernandes,Luis Pinto (2003)
PURPOSE: The plasmatic activity of the cholinesterase (CHE) and the liver mitochondrial function, expressed by the ratio of respiratory control (RCR), were studied during normothermic ischemia. METHODS: Sixteen adult mongrels, eight females and eight males were submitted to ischemia by clamping of the hepatic artery, portal vein and infrahepatic inferior vena cava, infra-hepatic, for two h, follwed by reperfusion for 1 h. The CHE and the mitochondrial function were evaluated at 60 and 120 min. of ischemia and at 15 and 60 minutes of reperfusion. RESULTS: The CHE decreased, significantly, during ischemia and in reperfusion. The RCR was decreased at 120 min. of ischemia, returning to the initial values on reperfusion. CONCLUSION: In this study, the CHE was a sensitive indicator of ischemic injury , suggesting irreversibility of ischemia injury. The RCR, by other side, showed a greater sensibility than the CHE in detection sense, during the studied period, the reversibility of the hepatic ischemic injury.